Essays on the Economics of Mitigating Climate Change - Hänsel, Martin Christopher (2018)
This doctoral thesis addresses central aspects of climate change economics including economic damages from climate change, discounting and intergenerational equity as well as sustainability in the light of increasing scarcity of non-market goods. Chapter 2 studies how the optimal global effort to mitigate carbon dioxide depends on conceptions of intergenerational equity by avoiding explicit discounting choices, but instead directly specifying alternative intertemporal distributions of well-being. The advantage of this approach is that it becomes very clear that the social cost of carbon is largely determined by normative conceptions of intergenerational distributive justice. Chapter 3 is concerned with the increasing scarcity of non-market goods due to climate change. It provides a comprehensive analysis of the change in the relative price of non-market goods in terms of market goods, its determinants and its impact on climate policy evaluation. For the central calibration neglecting relative price changes would lead to a considerable underestimation of the social cost of carbon of almost 50 percent for the current generation. The changing relative price of non-market goods in terms of market goods is of considerable magnitude compared to established determinants of economic evaluation. Chapter 4 assesses how economic damages from climate change can be mitigated when global warming interacts with other global and local environmental change within a national economy. It describes a developing economy that depends on agriculture and fisheries to study optimal and second-best environmental policy in the face of interacting external effects of ocean acidification, global warming and eutrophication. The last chapter of my dissertation reveals that although climate change is a global phenomenon and only a global solution can tackle it entirely, it can be vital to design national policy instruments that capture regional distinctiveness of environmental change under increasing carbon dioxide levels.